2013
DOI: 10.3389/fnbeh.2013.00065
|View full text |Cite
|
Sign up to set email alerts
|

Full body illusion is associated with widespread skin temperature reduction

Abstract: A central feature of our consciousness is the experience of the self as a unified entity residing in a physical body, termed bodily self-consciousness. This phenomenon includes aspects such as the sense of owning a body (also known as body ownership) and has been suggested to arise from the integration of sensory signals from the body. Several studies have shown that temporally synchronous tactile stimulation of the real body and visual stimulation of a fake or virtual body can induce changes in bodily self-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 56 publications
7
117
5
Order By: Relevance
“…However, the insula which is implicated in proprioceptive drift (see above) is also associated with the sensation of cooling (Hua et al 2005); this region could be involved in the cooling of the counterpart real hand that can accompany feelings of ownership of a rubber hand (Moseley et al 2008). Further research could also explore whether individual differences in hypnotic suggestibility extend to the perceptual illusion of body swapping (Petkova et al 2011;Salomon et al 2013). An interesting research question is whether hypnotic procedures (Deeley et al 2013a;Walsh et al 2014b) would further modulate performance during the RHI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the insula which is implicated in proprioceptive drift (see above) is also associated with the sensation of cooling (Hua et al 2005); this region could be involved in the cooling of the counterpart real hand that can accompany feelings of ownership of a rubber hand (Moseley et al 2008). Further research could also explore whether individual differences in hypnotic suggestibility extend to the perceptual illusion of body swapping (Petkova et al 2011;Salomon et al 2013). An interesting research question is whether hypnotic procedures (Deeley et al 2013a;Walsh et al 2014b) would further modulate performance during the RHI.…”
Section: Discussionmentioning
confidence: 99%
“…Self-identification (measured by using questionnaires) was significantly stronger after synchronous than asynchronous visuo-tactile stroking. As for the RHI, self-identification with the avatar decreased skin temperature at the level of the participant's body [97] and reduced the participant's pain perception [95]. In addition, the full-body illusion was characterized by errors in self-localization in space.…”
Section: Investigating Whole-body Representationsmentioning
confidence: 99%
“…In addition, previous research has argued that drops in body / finger temperature can reflect a psychophysiological anxiety response (Vinkers, et al, 2013), and this has been shown for non-clinical samples in relation to body illusions (full body illusions: Salomon et al, 2013; the RHI: Moseley et al, 2008;Kammers et al, 2011;Thakkar et al, 2011: though see also Hohwy & Paton, 2010;Paton et al, 2012 for failures to replicate). Therefore, finger temperature was measured as an additional objective index of threat-related anxiety, via a separate channel on the same MP36R unit described above.…”
Section: Finger / Body Temperaturementioning
confidence: 99%
“…Research has argued that the hypothalamus and preoptic area (PO) play crucial roles in effective body temperature regulation, and a wealth of research has explored thermoregulation with respect to behaviour such as psychological reactivity to stress (Hammel, 1968;Nagashima, Nakai, Tanaka, & Kanosue, 2000;Oka, 2015;Oka, Oka & Hori, 2001). Indeed, drops in finger temperature have been associated with fear / anxiety responses (Vinkers et al, 2013), and have been demonstrated under body-illusion conditions (full body illusions: Salomon, Lim, Pfeiffer, Gassert & Blanke, 2013; the Rubber-hand illusion, RHI: Moseley et al, 2008;Kammers, Rose, & Haggard, 2011;Thakkar, Nichols, McIntosh, & Park, 2011: though see also Hohwy & Paton, 2010;Paton, Hohwy, & Enticott, 2012 for failures to replicate). This has led some researchers to suggest that such drops in temperature could also be used as a reliable index of fear processing, and that temperature regulation must therefore involve higher, top-down cognitive processing between physiological regulation of the physical self and the conscious 'self' (Moseley et al, 2008).…”
Section: Uncomfortably Numb 11mentioning
confidence: 99%